Non-human Subalterns in Helon Habila's Oil on Water and Lawrence Amaeshi's Sweet Crude Odyssey - Chukwulobe, Innocent Chimezie; Zainal, Zainor Izat (Universiti Putra Malaysia Press, 2022)
This study explores the environmental challenges of the Niger Delta area of Nigeria especially as it affects non-humans as a subaltern group. The environmental challenges and devastation of the region is consequent upon the unregulated and unprofessional exploitation of petroleum product. Over the years, the environmental devastation by multinational oil firms in the Niger Delta region has gained prominent attention from Nigeria literary writers and critics. However, it is worthy of note that most of these writers and critics are majorly interested in the negative or positive effects of oil exploration and exploitation on humans. They either highlight the benefits of the venture or lament its negative effects on human’s means of subsisting in the region. This study will therefore shift attention to the representation of non-humans in Nigerian literary production, and analyse how the exploration and exploitation of petroleum products in the Niger Delta affects non-humans in the region as depicted in the Nigerian novels that serves as primary texts for this study. To do this effectively, we shall examine the relationship that exists between humans and non-humans as portrayed in Helon Habila’s Oil on Water (2012) and Lawrence Amaeshi’s Sweet Crude Odyssey (2017) as well as advocate for environmental justice for the subalterns. The analysis shall be anchored on the subaltern theory which we shall draw upon to include non-humans in the class of subalterns and we shall also draw instances from the novels to justify the classification of non-humans as ecological subalterns. Above all, we propose Murray Bookchin’s social ecological theory as a base to advocate for justice for the subalterns. The study found that imminent danger abounds if urgent measures are not taken to care for and protect non-human members of the ecology.